2013
DOI: 10.1007/s10616-013-9542-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of TLR7/8, TLR9 agonists and CD40 ligand on the transformation efficiency of Epstein-Barr virus in human B lymphocytes by limiting dilution assay

Abstract: Infection of human B cells with Epstein-Barr virus (EBV) induces polyclonal activation in almost all infected cells, but a small proportion of infected cells are transformed to immortalized lymphoblastoid cell lines. Since B cells are activated also by CD40 ligand (CD40L) and Toll-like receptor (TLR) agonists via a similar signaling pathway, it is likely that costimulation through these molecules could result in synergistic enhancement of the transformation efficiency of EBV. In this study, the stimulatory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…We also performed a traditional and reliable limiting dilution assay (LDA) to determine the fraction of CSCs in each subpopulation. The LDA results revealed the frequency of sphere formation, providing useful information for interpreting the composition of the mixed population of CSCs [23, 46]. Our current data showed that Lgr5-positive subpopulations possessed a higher percentage of CSCs than did Lgr5-negative subpopulations.…”
Section: Discussionmentioning
confidence: 58%
“…We also performed a traditional and reliable limiting dilution assay (LDA) to determine the fraction of CSCs in each subpopulation. The LDA results revealed the frequency of sphere formation, providing useful information for interpreting the composition of the mixed population of CSCs [23, 46]. Our current data showed that Lgr5-positive subpopulations possessed a higher percentage of CSCs than did Lgr5-negative subpopulations.…”
Section: Discussionmentioning
confidence: 58%
“…Conversely, Smad4, a well-known tumour silencer and a major regulator of intracellular TGF-β1 signalling, was up-regulated after knockdown of KLF4 expression ( Figure 1A,B). 20,24,25 Our data showed that the median frequencies were from 100/211 of CSCs-shCon cells to 100/566 of CSCs-shKLF4 cells in primary colorectal patient samples, and the median frequencies were decreased in Lgr5 + CD44 + EpCAM + cells from DLD-1 (100/484 vs 100/1304) cells after KLF4 knockdown ( Figure 1C). Because a sphere is composed of all descendants from a single CSC, the number of sphere reflects the CSC population 23 and CSC frequency can be estimated through the LDA.…”
Section: Klf4 Overexpression Facilitates Colorectal Cscs Stemness Pmentioning
confidence: 78%
“…Because concomitant infections can induce reactivation of the EBV lytic cycle [35], it is tempting to speculate that episodes of increased EBV load could coincide with common viral or bacterial infections inducing B cell activation in XIAP G466X patients. In a recent study, co-stimulation of cells PBMCs with Toll-like receptor (TLR)-7/8 and TLR-9 agonists increased significantly the frequency of EBV transformed B cells (P < 0·001) [36].…”
Section: Discussionmentioning
confidence: 98%